Slope-intercept form is
y=mx+b
so your equation is already in that form
so for the y-intercept you have
(0,?) because the first number is always zero
Then the second number is 6 because y is equal to b.
then for the x-intercept you have
(?,0) because the second number is always zero
To get the first number you plug in zero for y
so 0=-2x+ 6
and solve for x
the answer is x=3 so that is your second number
then graph your two points and draw a slop through it
hope i helped!!
2006-12-10 05:15:56
·
answer #1
·
answered by Anonymous
·
0⤊
1⤋
Something I want you to keep in mind is relating words to "parallel" and "perpendicular" when it comes to lines.
Parallel - "Same slope"
Perpendicular - "Negative reciprocal"
Since we want the equation of a line parallel to the line y = -2x+6, notice that the equation of that line is y = mx + b, where m is the slope. Therefore, m = -2.
This means our new line will have that same slope m = -2.
Remember that the formula for slope is
m = (y2 - y1) / (x2 - x1)
What we do at this point is plug in the values for this slope formula as if we were calculating the slope from (-2,1), which is our given point, to (x,y), which is our general point.
Therefore, x1 = -2, x2 = x, y1 = 1, y2 = y, and m = -2.
Therefore,
-2 = (y - 1)/(x - (-2))
-2 = (y - 1)/(x + 2)
-2(x+2) = y - 1
-2x + 2 = y - 1
-2x + 3 = y
Therefore, y = -2x + 3 is the equation of our line.
2006-12-10 13:18:47
·
answer #2
·
answered by Puggy 7
·
0⤊
0⤋
Parallel lines always have the same slope.
The line y = -2x + 6 has a slope of -2.
So the equation you seek will look a little like:
y = -2x +b.
So what is b, you ask?
Since the line whose equation we seek passes through the point (-2, 1), then x=-2 and y=1 is a solution to the equation.
Thus the following must hold:
1 = (-2)(-2) + b.
The algebra is simple from here:
1 = 4 + b,
b = -3.
Hence, the equation you seek is:
y = -2x - 3.
Feel free to email me for clarifications.
2006-12-10 13:16:49
·
answer #3
·
answered by Bugmän 4
·
0⤊
0⤋
Ok, if you have a line parrallel to another line, they have the same slope. So, you need to use the slope from y = -2x+6 (slope is negative 2) and the new point (-2,1). Put this into point-slope form of a line; i.e.:
y-y1 = m(x-x1) where m=slope, and (x1,y1) is the point you have to use.
2006-12-10 13:22:53
·
answer #4
·
answered by Jayne K 1
·
0⤊
0⤋
The slope is the same, -2
The point where the straight line intercepts the y axis is a
y = - 2x + a
This line passt through the point (-2,-1)
-1 = -2*(-2) + a
And then you calculate a, you plug it into the equation.
Ana
2006-12-10 13:15:59
·
answer #5
·
answered by Ilusion 4
·
0⤊
2⤋